Traditional modernity: the cultural imprint of the Brazilian economy - Valarini, Elizângela (Global economic elites and the new spirit of capitalism, 2024)
The most relevant empirical studies about Brazilian economic elites and management date back to the 1960s and 1970s. These focus on the recruitment, ethnical and social origins as well as on the capitalistic mentality e.g. mindset of Brazilian managers in the industrial sector. They focused on the influence of the industrial elite on the Brazilian’s economic development in the context of growing industrialization.
Gesehen am 28.06.2024